CREATING A SOCIAL JUSTICE TROUGH ZAKAT AND ITS RELEVANT TO POVERTY ALLEVIATION: A PERSPECTIVE OF ABUL A’LA AL-MAUDUDI - Hafandi, Akhmad; Helmy, Masdar (An-Nisbah: Jurnal Ekonomi Syariah, 2021)
This paper aims to reveal Al Maududi’s thoughts related to the concept of social justice which is proxied in the management of zakat. His thoughts emphasis on the entire economic scheme developed under the principles of sharia (Islamic law), projecting an internally balanced economic system and totally not accepting capitalism or communism. He explicitly stated that the embodiment of justice (a’dl) and welfare (falah) as a means of seeking God’s blessings (fadhl al-Allah) through the determination of its main goals using the maqasid of sharia. The results of this literature study are able to reveal that zakat philanthropy can carry out several main functions of modern public finance related to social security rights in the form of health, education, food, housing, and public transportation. Zakat is also able to reduce social inequality that arises as a result of human exploitative economic behavior and becomes an effort to achieve social justice.